Optimizacija sestave mešanih portlandskih cementov glede na proizvodne stroške - Vuk, Tomaž (Kovine zlitine tehnologije, 1999)
An optimization of composite Portland cements composition was performed in order to reduce costs of production. 28 different cements were prepared in a laboratory mill. Compressive strengths after 28 days for each sample were determined. A response surfae function for compressive strength prediction was obtained. Production costs were determined as the sum of costs for raw materials and estimated costs for grinding. Computer program SOLVER (EXCEL) was used for the determination of cements with minimal production costs in different compressive strength classes. These results will be used as a starting point for the development of new types of composite Portland cements in Salonit Anhovo cement factory.
Keywords: cementi; proizvodnja; stroški; optimizacija